CROWDFUNDING – AN ALTERNATIVE FOR FINANCING A BUSINESS - CLAUDIA ISAC (Annals of the University of Petrosani: Economics)
One of the most important trends in the world of the Internet in the past two years was the process of crowdfunding. In the paper I presented several defining elements of this financing practice of social projects or companies, ranging from a quick evolution over time and a presentation of the theoretical concept to a statistical presentation of the number of crowdfunding platforms and also of the amounts collected worldwide, thanks to them. In the second part of the paper we presented the three major platforms in Romania and some of the projects financed entirely due to their help. At the end of the paper one may find legislative guidance regarding crowdfunding in the USA, Europe and Romania.